(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
Nouns are a fundamental component of language, representing people, places, objects, and abstract concepts. Their classification into subcategories—such as common and proper nouns, countable and uncountable nouns, and collective nouns—highlights the complexity of this grammatical category. This article provides a comprehensive analysis of nouns, examining their definitions, classifications, morphological and syntactic characteristics, and functions within sentences. By exploring nouns through various linguistic frameworks, this study enhances our understanding of their pivotal role in communication. A deeper insight into nouns is essential for linguists and language learners alike as they navigate the intricacies of language structure and use. Through this investigation, we aim to contribute to broader discussions in linguistics, language acquisition, and pedagogy